The rise of Pretoria urban vanguard : [r]ecalibrating a series of urban voids and measuring their impact on creative led urban [r]evolution - White, G.T. (Gary) (University of Pretoria, 2016)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2015.